Anti-NMDAR Encephalitis With Serial Negative MRI Findings: An Evaluation Using Autoimmune Psychosis Criteria - Satoshi Saito; Go Taniguchi; Chihiro Nakata; Hideo Kato; Mao Otake; Masahiro Umeda; Yuichiro Fuji; Eiji Nakagawa (Case Reports in Neurological Medicine)
Autoimmune psychosis criteria have been proposed for autoimmune encephalitis with prominent psychiatric symptoms as an alternative to biomarker-based diagnostic approaches such as the Graus criteria. We present a case of anti-N-methyl-D-aspartate receptor (NMDAR) encephalitis that was initially misdiagnosed as a psychiatric disorder due to serial negative MRI findings and subsequently re-evaluated correctly using autoimmune psychosis criteria. A 15-year-old male developed sudden-onset generalized convulsive seizures that increased progressively in frequency and fluctuating psychiatric symptoms that gradually worsened to include reduced reactivity, language deterioration, and catatonia. On admission, both brain MRI and cerebral spinal fluid (CSF) findings were unremarkable; however, autoimmune encephalitis was strongly suspected based on autoimmune psychosis criteria and subsequently confirmed by detection of oligoclonal bands (OCBs) and anti-NMDAR antibodies in the serum and CSF. Repeated steroid pulse therapy resulted in significant clinical improvement. The patient met multiple autoimmune psychosis criteria, including subacute onset of psychiatric symptoms, catatonia, disproportionate cognitive dysfunction, decreased level of consciousness, and the emergence of seizures. These features are not typically present in primary psychiatric disorders. Anti-NMDAR encephalitis can present with a variety of symptoms, complicating its differentiation from primary psychiatric conditions. The application of autoimmune psychosis criteria may serve as a valuable diagnostic aid, particularly when MRI findings are repeatedly negative.